Proceso de atención de enfermería en neonato con diagnóstico de impétigo. - Cerezo Gonzales, Rosa Johanna (2021)
Impetigo, a highly contagious bacterial infection that affects the superficial layers of the skin, is one of the most common skin infections in children ages 2 to 5, but it can occur in newborns and school children. It is caused by microorganisms such as: Streptococcus pyogenes and Staphylococcus aureus. It is clinically characterized by the appearance of small pustules, blisters or vesicles that, when breaking and drying, form meliceric crusts. This infection can occur on previously healthy skin or injured skin such as wounds or erosions and insect bites. Impetigo is most common in the warmer months of the year (tropical climates) and in places with little access to health care and poor hygienic conditions. A 22-day-old newborn was admitted to neonatology presenting erythematous, bullous, scaly skin. Very irritable when handling. This was eventually diagnosed as bullous impetigo caused by Staphylococcus aureus. The skin lesions diminished and dried over the days, with the due care given to the patient and the administration of the prescribed antibiotics. Carrying out this case study is to put into practice all the knowledge acquired and establish the necessary nursing care plan so that together with medical treatment, skin infection can be fought and complications reduced.